2022
DOI: 10.1177/00219983221077485
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of in-plane compression failure mechanism in carbon fiber braided composite with different off-axial angles

Abstract: This paper focuses on the in-plane compression mechanism of two-dimensional biaxial braided composite laminates under quasi-static compression and dynamic compression. Three types of specimens with different off-axial angles in respect of OA00, OA60, and OA90 were employed for compression experiments. The surface damage process of the specimen was recorded using optical camera and infrared thermal imaging technology. The internal damage morphology of the tested specimens was analyzed by X-ray computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…An in-depth understanding of the effects of low-velocity impact on the structural properties of composites is important for the practical application of composites. The mechanical properties of the composite materials have been 1 studied in depth, [37][38][39][40][41] Liu et al, 42 Guynn et al 43 and Soutis et al 44 studied the compression damage of open-cell CFRP laminates from a micromechanical point of view and found that for open-cell CFRP structures, the initial damage tends to arise from the edge of the hole and then expands steadily until a critical size is reached. Hallet et al, 45 Kumar et al 46 and Liu et al 42 investigated the effects of hole size, hole shape, hole size shape and distribution on CFRP failure modes and failure characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth understanding of the effects of low-velocity impact on the structural properties of composites is important for the practical application of composites. The mechanical properties of the composite materials have been 1 studied in depth, [37][38][39][40][41] Liu et al, 42 Guynn et al 43 and Soutis et al 44 studied the compression damage of open-cell CFRP laminates from a micromechanical point of view and found that for open-cell CFRP structures, the initial damage tends to arise from the edge of the hole and then expands steadily until a critical size is reached. Hallet et al, 45 Kumar et al 46 and Liu et al 42 investigated the effects of hole size, hole shape, hole size shape and distribution on CFRP failure modes and failure characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber-reinforced composites have gradually replaced metal materials in aerospace because of their excellent properties such as high specific strength, and high specific stiffness. [1][2][3][4][5][6][7][8] The crashworthiness of the aircraft is closely related to the design of the composite energy-absorbing structure, which directly affects the safety of the occupants. [9][10][11][12] In collision accidents, the composite structure can dissipate a large amount of impact kinetic energy through complex failure modes such as fiber matrix damage, buckling failure, delamination, and folding.…”
Section: Introductionmentioning
confidence: 99%